Strategies for translating idioms in The Murder on the Links into Arabic - Obaid H., Al Harbi Emad (2022)
Idiom is the most difficult parts in semantic area for both English and Arabic. Idioms are difficult to translate because of their unpredictable meaning and grammar. This study focuses on the strategies of translating idioms in Christie's novel ‘The Murder on the Links’ into Arabic. Three objectives are pursued through this study. First, to identify the types of idioms in Christie's novel ‘The Murder on the Links’. Second, to investigate the strategies used by the translator when translating idioms into Arabic. Third, to examine the implications of using these strategies when deducing the meanings of idioms translated into Arabic. The theoretical part is based on Fernando (1996) and Baker (2011). In this study, a qualitative-analytical approach is adopted to identify the types of idioms and the strategies used to translate idioms. The analytical part is based on the novel ‘The Murder on the Links’by Christie and the Arabic translation by Elbaradei. The data of the study consists of 90 idioms extracted from the novel ‘The Murder on the Links’. The process of extracting the data for the study was based on the thematic analysis approach. The results of the study showed that there are three types of idioms; literal idioms, pure idioms, and semi-idioms. In translating idioms from English into Arabic, the translator employed four strategies, namely, using an idiom with an idiom of similar meaning but dissimilar form, an idiom with an idiom of similar meaning and form, paraphrasing, and omission. Although previous studies have demonstrated that paraphrasing was the most common strategy, this study showed that the strategy of translating an idiom related to time, beliefs, politeness, and disagreement, while the strategy of omission was used in translating idioms related to beliefs and describing eventswith an idiom of similar meaning but dissimilar form was the most commonly used strategy when translating idioms from English into Arabic. The results also showed that when deducing the meaning of the idioms translated into Arabic, most of the idioms were explicitly rendered. In terms of themes, especially in this detective novel, the results revealed that most of the idioms related to describing people were translated using the strategy of translating an idiom with idioms of similar meaning and form. On the other hand, the strategy of translating an idiom with idioms of similar meaning but dissimilar form was used in translating idioms related to the description of persons, events, and actions. The strategy of paraphrasing was used in translating idioms related to time, beliefs, politeness, and disagreement, while the strategy of omission was used in translating idioms related to beliefs and describing events.